FACTORS AFFECTING MOTHER OF CHILDREN UNDER FIVE YEARS OLD’S ACTIVITY TO POSYANDU - Wibowo, Syifa Sofia; Octaviani, Dhita Aulia; Wahyuni, Sri (Postgraduate Program , Poltekkes Kemenkes Semarang, 2021)
ABSTRACT The 2017 Indonesian Health Profile shows the number of posyandu in Indonesia has 164,867 (56.57%) active posyandu. However, the quantity of posyandu is not in line with the quality of utilization of the posyandu. In 2017 there were only 89,070 (82.6%) toddlers weighed in posyandu from 107,846 toddlers who were there. This amount is far from the target of visiting toddlers in Central Java Province, which is equal to 90%. The purpose of this study was to determine the factors that influence the activity of mothers of children under five to posyandu, including factors of education, employment, age and knowledge of children under five at the posyandu. This research was carried out at the Posyandu in the Pandean Lamper Sub-District of Semarang City in March 2019. This type of research was analytic observational with a cross sectional design. The study population was mothers of children under five (1-5 years). Sampling using proportionate stratified random sampling. The relationship of education and activity of mothers of children under five has a moderate correlation with a value of 0.580 and the relationship between knowledge and activity of mothers of children under five has a strong correlation with a value of 0.675. In the future, it is expected that mothers of toddlers always maintain the activity of posyandu and cadres always provide motivation to mothers to attend the posyandu activities. Conclusion: the longer the mother under five takes the level of education and the higher the knowledge of the mother under five, the higher the activity of the mother of the toddler to the posyandu.